Faktor – Faktor yang Mempengaruhi Minat Belajar Bahasa Arab Siswa SMP Muhammadiyah 7 Madrasah Tsanawiyah - Habibah Khairani; Ariza Amalia; Regina Valda Garzita; Fadhilatul Husna; Sakholid Nasution (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this study was to determine the factors that influence interest in learning Arabic at SMP Muhammadiyah 7 Madrasah Tsanawiyah and the teacher's efforts to improve this interest. This qualitative study describes and analyzes the phenomenon in Arabic language learning in the classroom. To collect data, observation of the learning process, interviews with students, Arabic teachers, and the head of the madrasah, and documentation were used. This study used students and Arabic teachers as data sources. The results showed that several factors that influenced students' interest in learning Arabic at SMP Muhammadiyah 7 were learning methods, educational facilities, family and school environments, the ability to read and write the Qur'an, students' educational backgrounds, and teacher character. To improve students' interest in learning Arabic, teachers did the following: providing opportunities for students to participate actively, providing exercises or assignments, using appropriate methods, connecting lessons with what they already knew, and explaining the objectives of the lesson before the lesson began.